2020
DOI: 10.1007/s11229-020-02558-7
|View full text |Cite
|
Sign up to set email alerts
|

Truth, fallibility, and justification: new studies in the norms of assertion

Abstract: This paper advances our understanding of the norms of assertion in two ways. First, I evaluate recent studies claiming to discredit an important earlier finding which supports the hypothesis that assertion has a factive norm (i.e. assertions should express truths). In particular, I evaluate whether it was due to stimuli mentioning that a speaker's evidence was fallible. Second, I evaluate the hypothesis that assertion has a truth-insensitive standard of justification. In particular, I evaluate the claim that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…[Yes/No], subjects overwhelmingly selected the latter option (No), even when different factors were manipulated (the control questions, the stakes, and the response options), providing apparently robust evidential support for factive accounts. Other studies found similar results, accumulating an impressive body of evidence supporting factive accounts of assertion in general (Turri, 2013(Turri, , 2017b(Turri, , 2018(Turri, , 2020 and the knowledge rule in particular (Turri, 2014a(Turri, , 2014b(Turri, , 2015(Turri, , 2016Turri, Friedman & Keefner, 2017;Turri & Park, 2018;Turri & Buckwalter, 2017;Turri, 2018).…”
Section: Experimental Research On the Norm Of Assertionsupporting
confidence: 57%
“…[Yes/No], subjects overwhelmingly selected the latter option (No), even when different factors were manipulated (the control questions, the stakes, and the response options), providing apparently robust evidential support for factive accounts. Other studies found similar results, accumulating an impressive body of evidence supporting factive accounts of assertion in general (Turri, 2013(Turri, , 2017b(Turri, , 2018(Turri, , 2020 and the knowledge rule in particular (Turri, 2014a(Turri, , 2014b(Turri, , 2015(Turri, , 2016Turri, Friedman & Keefner, 2017;Turri & Park, 2018;Turri & Buckwalter, 2017;Turri, 2018).…”
Section: Experimental Research On the Norm Of Assertionsupporting
confidence: 57%
“…[Yes/No], subjects overwhelmingly selected the latter option (No), even when different factors were manipulated (the control questions, the stakes, and the response options), providing apparently robust evidential support for factive accounts. Other studies found similar results, accumulating an impressive body of evidence supporting factive accounts of assertion in general (Turri, 2013(Turri, , 2017b(Turri, , 2018(Turri, , 2020 and the knowledge-rule in particular (Turri, 2014a(Turri, , 2014b(Turri, , 2015(Turri, , 2016Turri, Friedman, & Keefner, 2017;Turri & Park, 2018;Turri & Buckwalter 2017;Turri, 2018).…”
Section: Experimental Research On the Norm Of Assertionmentioning
confidence: 59%
“…These results undermine a fundamental premise of Turri's (2013) This experiment shows, against the assertability assumption, that questions about what an agent 'should say' do not necessarily track assertability judgments, because of the ambiguity between a teleological and a deontological reading of the verb 'should'. This is a significant discovery, as the whole body of studies conducted by Turri and colleagues (Turri, 2013(Turri, , 2014a(Turri, , 2014b(Turri, , 2015(Turri, , 2016(Turri, , 2017b(Turri, , 2017a(Turri, , 2018(Turri, , 2020Turri & Buckwalter, 2017;Turri & Park, 2018) takes the assertability assumption for granted in interpreting the results of the experiments. While we are not claiming that the participants of all these studies must have interpreted the task in a way that is incompatible with the assertability assumption (e.g., teleologically rather than deontologically), our results highlight that the opposite cannot be taken for granted, so that the conclusions drawn in these studies rely on a demonstrably dubious premise.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations